Strengthening the Blue Economy through Marine, Coastal Resources and the Social Environment - Muliani Dwi Ujianti, Rizky; Novita, Mega; Burhanuddin, Aan (KnE Social Sciences, 2024)
The fisheries sector is a sector which supports Indonesia’s development, because the waters in Indonesia are wider than the land. Central Java is a region that has a long coastline stretching along the north coast and the south coast of Java. This supports the development of fisheries potential in Indonesia. Research on the blue economy theme for the fisheries sector is being promoted. The method used is an analysis of economic aspects in Central Java, especially people engaged in fisheries (GRDP and income per capita), potential fisheries resources, human resource potential (number of fish fishermen and cultivators), fisheries households, as well as aspects of production and value fisheries production. The results of this research can provide an overview of the potential of fisheries in Central Java to facilitate their management. The research results show that GRDP in the fields of fisheries, forestry, and agriculture during the 2018-2022 period was 3.23%-7.33%; the highest per capita expenditure in the food sector is used to purchase food, and non-food cost is for housing and household facilities. The highest fish resource potential is a small pelagic fish. The most increased fisheries production in 2022 in the Central Java region will be in Rembang and Pati Regencies which have coastlines and are coastal areas. Keywords: fisheries, blue economy, coastal resources, marine resources